Depth measurement of closely spaced surface cracks by the electric potential method - Shkatov, Petr; Lisitsyna, Irina; Sandulyak, Anna; Bulut, Hasan (E D P Sciences, 2017)
The study results are provided for the electropotential converter signals interacting with two closely spaced parallel surface cracks. The measurement scheme was studied with transducer electrodes placed at the vertices of the rectangle. Study results are important for depth measuring of the surface cracks of stress-corrosion origin.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY